13.3k views
2 votes
Write sin6x-sinx as a product.

User Fnkr
by
6.1k points

1 Answer

3 votes

Answer:


sin(6x) - sin(x)= 2cos((7x)/(2)) * sin((5x)/(2))

Explanation:

To write sin6x-sinx as a product , we use formula


sin(a) - sin(b)= 2cos((a+b)/(2)) * sin((a-b)/(2))

We have 6x in the place of 'a' and x in the place of b

Replace it in the formula


sin(a) - sin(b)= 2cos((a+b)/(2)) * sin((a-b)/(2))


sin(6x) - sin(x)= 2cos((6x+x)/(2)) * sin((6x-x)/(2))


sin(6x) - sin(x)= 2cos((7x)/(2)) * sin((5x)/(2))